The Right to Clothing in International Law, A Forgotten Right? - Stephen James; Amir Feizbakhsh (پژوهشهای حقوقی)
Clothing has long been considered one of the necessities of human life in many cultures. However, only a few documents and declarations of rights in the international and regional scene mention it. For example, the United Nations International Covenant on Economic, Social and Cultural Rights mentions the right to clothing in its eleventh article. But the importance of this right over other basic needs has been overlooked by the Committee which monitors the implementation of the Covenant. As the same way, international law practitioners and human rights scholars have also disregarded the right to clothing. Much research has been done on freedom of dress in the context of civil and political rights. But the right to adequate clothing has been surprisingly neglected among other economic, social, and cultural rights. The dressing of a person is not only related to his economic status, but also to his position in society. Furthermore, one's clothing affects one's cultural, sexual, and religious identity, as well as one's dignity and even one's health. The insignificant recognition of such a right in the legal sphere justifies its being considered a forgotten right.